If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(m + -5) + -4(-2m + -3) = 0 Reorder the terms: 3(-5 + m) + -4(-2m + -3) = 0 (-5 * 3 + m * 3) + -4(-2m + -3) = 0 (-15 + 3m) + -4(-2m + -3) = 0 Reorder the terms: -15 + 3m + -4(-3 + -2m) = 0 -15 + 3m + (-3 * -4 + -2m * -4) = 0 -15 + 3m + (12 + 8m) = 0 Reorder the terms: -15 + 12 + 3m + 8m = 0 Combine like terms: -15 + 12 = -3 -3 + 3m + 8m = 0 Combine like terms: 3m + 8m = 11m -3 + 11m = 0 Solving -3 + 11m = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 11m = 0 + 3 Combine like terms: -3 + 3 = 0 0 + 11m = 0 + 3 11m = 0 + 3 Combine like terms: 0 + 3 = 3 11m = 3 Divide each side by '11'. m = 0.2727272727 Simplifying m = 0.2727272727
| x/4=13/2 | | x-(-54)=51 | | 3x+15=27-4x | | z+19+4z-7+90=180 | | -4-6=-2 | | 19=y-5 | | 2x-11=-6(-1-4x)-5x | | x/9=42/54 | | z+12+4z-7=180 | | 14(x+7)=3(x+4) | | z+12=2(4z-7) | | 6+4(3-4x)=-2(1+3x) | | 15/3=x/5 | | 2(-2x-5)+4x=10 | | -5(5y-5)+2(2y+5)= | | (2x+5y)+(x+y)=1 | | z+12=4z-7 | | 90+90+(2x-4)+(3x-29)=360 | | 45x-9y=18 | | -9=3x+5 | | 4x^2+45=20x | | 848/0 | | w(w-6)=0 | | 8t+2(1-5t)= | | 4x^2+28x=-61 | | -3x+5+(-4x+6)+7x=(2.4x-3.7)(-3)-7.2x+11 | | 2/5=x/25 | | 2(3x+1)+x-3(2x+1)=x+4(x-1)-(4x+3) | | -1(3x+4)-4x=-2(4x-3)+2 | | 5x=(400/4) | | 2x+x-3+x=22 | | y=x^2-8x+k |